Analisis Pengaruh Aspek Perawatan Kesehatan terhadap Kualitas Hidup Pasien Kanker Stadium 3 dan 4 - Dwi Zulfiata Iriandana; Dewi Martha Indria; Erna Sulistyowati (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Background: Cancer is the main problem causing high morbidity and mortality in Indonesia. Cancer patients’ have been suffering low quality of life which there have been many factors influencing such as physical, psychological, and economic conditions. This study aimed to determine the effects of treatment duration, patient hospital visit frequency, chemotherapy and/or radiotherapy frequency. We then compared them with quality of patients’ life.Methods: This cross-sectional analytic study was a total sampling who the 3rd and 4th cancer patients stadium who have been registered at the Saiful Anwar Hospital medical record during year 2015 to 2019. These secondary data were then confirmed with European Organization for Research and Treatment of Cancer Quality of Life Questionnaire 30 (EORTC QLQ30) to identify the quality of patients’ life. The data was analyzed by fisher exact where the significance value was considered at p <0,05.Results: We found that most of the patients’ quality of life were in the medium classification. There was no significant value between duration of treatment and quality of patients’ life (p 0,493). Similar results were also found in the comparison between frequency of patients’ hospital visit and quality of patients’ life (p 1,000). Frequency of chemotherapy and/or radiotherapy and quality of patients’ life were insignificant as well (p 1,000).Conclusion: The duration of treatment, frequency of patients’ hospital visit, frequency of chemotherapy and/or radiotherapy caused no changes in the quality of patients’ life in Malang. Further study would be beneficience to establish using more accurate instruments to assess the quality of cancer patients’ life based on their therapy.Keywords: Cancer patients, therapy, quality of patient’s life